Virus-driven autoimmunity and lymphoproliferation: the example of HCV infection. (January 2014) - Zignego, Anna Linda; Gragnani, Laura; Piluso, Alessia; Sebastiani, Marco; Giuggioli, Dilia; Fallahi, Poupak; Antonelli, Alessandro; Ferri, Clodoveo
<x xml:space="preserve">Abstract</x> HCV chronic infection is characterized by possible development of both hepatic and extrahepatic manifestations. The infection by this both hepatotropic and lymphotropic virus is responsible for polyoligoclonal B-lymphocyte expansion, leading to several immune-mediated disorders. Mixed cryoglobulinemia syndrome that in some cases may evolve to frank B-cell non-Hodgkin's lymphoma is the prototype of HCV-driven autoimmune and lymphoproliferative disorders. The HCV oncogenic potential has been suggested by several clinicoepidemiological and laboratory studies; it includes hepatocellular carcinoma, B-cell non-Hodgkin's lymphoma and papillary thyroid cancer. The definition HCV syndrome refers to the complex of HCV-driven diseases; these latter are characterized by heterogeneous geographical distribution, suggesting a role of other important genetic and/or environmental cofactors. The natural history of HCV syndrome is the result of a multifactorial and multistep pathogenetic process, which may evolve from mild manifestations to systemic autoimmune disorders, and less frequently to malignant neoplasias. The present updated review analyzes the clinical and pathogenetic aspects of the main HCV-associated diseases.